Empowerment and poverty reduction - The international bank for reconstruction and development (Washington (State) : The world bank, 2002)
Trata del empoderamiento de la gente pobre y la inversión en sus prioridades como una de dos áreas prioritarias de apoyo del Banco a los países clientes.
1. The meaning of empowerment 2. Governance and Growth
incluye índice
Col. Admon
Keywords: 1. LOCAL ORGANIZATIONAL CAPACITY 2. IMPROVED NATIONAL GOVERNANCE